1998
DOI: 10.1038/sj.onc.1201667
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the cdk inhibitor p21 gene during cell cycle progression is under the control of the transcription factor E2F

Abstract: The control of cell cycle progression is orchestrated by an extraordinary diverse and dynamic in function group of proteins. Critical in the progression are the actions of the E2F family of transcription factors which regulate the expression of genes necessary for the G 1 /S transition and the WAF/CIP/KIP family of cdk inhibitors which can inhibit cell cycle progression. In this report, we have identi®ed E2F binding sites in both the human and mouse p21 promoters that bind E2F protein complexes from nuclear ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
86
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 49 publications
7
86
0
Order By: Relevance
“…It is well documented that factors other than p53 can induce p21 gene expression (Li et al, 1995;Halevy et al, 1995;Qiu et al, 1996;Greenhalgh et al, 1996;Billion et al, 1996;Lee et al, 1998). Our data suggest that E2F-1 may have a similar ability to induce p21 under certain circumstances and is in agreement with a recent study where E2F-1 was found to transactivate p21 (Hiyama et al, 1998). Although one study reported that p21 growth arrest fails to protect gliomal cells from E2F-1-mediated apoptosis (GomezManzano et al, 1999), a growing body of evidence now points to an opposing relationship between E2F-1 and p21 in both cell cycle control and induction of apoptosis (Chen et al, 1995;Shiyanov et al, 1996;Dimri et al, 1996;Hiyama et al, 1998;Delavaine and La Thangue, 1999).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It is well documented that factors other than p53 can induce p21 gene expression (Li et al, 1995;Halevy et al, 1995;Qiu et al, 1996;Greenhalgh et al, 1996;Billion et al, 1996;Lee et al, 1998). Our data suggest that E2F-1 may have a similar ability to induce p21 under certain circumstances and is in agreement with a recent study where E2F-1 was found to transactivate p21 (Hiyama et al, 1998). Although one study reported that p21 growth arrest fails to protect gliomal cells from E2F-1-mediated apoptosis (GomezManzano et al, 1999), a growing body of evidence now points to an opposing relationship between E2F-1 and p21 in both cell cycle control and induction of apoptosis (Chen et al, 1995;Shiyanov et al, 1996;Dimri et al, 1996;Hiyama et al, 1998;Delavaine and La Thangue, 1999).…”
Section: Discussionsupporting
confidence: 83%
“…Recently, E2F-1 has also been shown to upregulate p21 and subsequently, E2F-1 activity is inhibited, thus forming a negative feedback loop (Hiyama et al, 1998). To further investigate the mechanisms of E2F-1 and p53 interactions, we probed for p21.…”
Section: Upregulation Of P21 Waf1/cip1mentioning
confidence: 99%
“…The p21 WAF1/CIP1 accumulation may also be induced by the activation of alternative pathways. For instance, it was demonstrated that the p21 WAF1/CIP1 gene is regulated by the transcription factor E2F, which is normally activated in HPV-infected cells (Hiyama et al, 1998). Another possibility would be the transactivation pathway through p53 (Macleod et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Interestingly, a recent study demonstrated that E2F -1 directly transactivates p21, and subsequently, E2F -1 transcriptional activity is inhibited. 27 Collectively, the evidence suggests a feedback loop mechanism between E2F -1 and p21 with apparently opposing activities that involve both direct and indirect interactions. 26,28,29 The mechanism( s ) of E2F -1 -mediated apoptosis are not completely elucidated.…”
mentioning
confidence: 99%